Venous thromboembolism associated with acute cytomegalovirus infection: epidemiology and predisposing conditions. Issue 4 (3rd July 2016) - Yildiz, Halil; Zech, Francis; Hainaut, Philippe
Abstract : Background: Venous thromboembolism has been reported in association with cytomegalovirus (CMV) infection both in immunocompromised and immunocompetent patients. In this population, it is yet undetermined whether CMV alone provokes VTE or other predisposing conditions are involved. Materials and methods: 1007 VTE patients consecutively recruited in one academic hospital were analyzed retrospectively in order to identify acute CMV infection. Acquired and inherited risk factors were screened. Only adults and immunocompetent patients were included. Results: Among 1007 consecutive VTE patients, we identified 10 patients with synchronous acute CMV infection. Patients with coexistent VTE and acute CMV infection were younger (37.5 years vs. 56.6 years; p  = 0.0088) and exhibited a female predominance (90% vs. 56%; p  = 0.026), in comparison to the whole cohort. Hereditary thrombophilia was identified in 9 out of 10 patients. Acquired risk factors for VTE like estrogens administration and pregnancy were equally prevalent in patients with and without CMV infection. Conclusion: Acute CMV infection is a potential contributor to VTE whenever other prothrombotic conditions are required. This should help clinicians to privilege a limited duration of anticoagulant treatment like in other provoked VTE.